Edaravone for patients with amyotrophic lateral sclerosis: a systematic review and meta-analysis - Huang, Shi-Le; Shen, Yin-Li; Peng, Wen-Yan; Ye, Kun; Zheng, Hui (Acta neurologica Belgica, 2024)
Background and objective The effectiveness and long-term efficacy of edaravone, a recommended treatment for amyotrophic lateral sclerosis (ALS), has not been examined in real-world settings. This study aims to evaluate the effectiveness and long-term efficacy of edaravone. Methods The OVID Medline, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and Web of Science databases were searched for articles published between January 1, 2000, and May 1, 2023. Two investigators independently screened the retrieved articles for randomized controlled trials (RCTs), cohort studies, or single-arm trials that evaluated the effect of edaravone on amyotrophic lateral sclerosis (ALS). The risk of bias was evaluated using the revised Cochrane Risk-of-Bias (RoB 2.0) tool for randomized controlled trials (RCTs) and the Risk-of-Bias In Non-randomized Studies of Interventions (ROBINS-I) tool for observational studies. The primary outcome was the ALSFRS-R score assessed at month 6, with secondary outcomes including the ALSFRS-R scores evaluated at months 9, 12, and 18, forced vital capacity (FVC), and adverse events. The certainty of evidence was assessed using the GRADE approach. Results The analysis included 16 studies with a total of 4828 participants. Among these, four were randomized controlled trials (RCTs) and 12 were observational studies. Of the RCTs, four were rated as having a low risk of bias, while six of the observational studies were rated as having a low risk of bias. Edaravone was associated with slightly slower progression in the reduction of ALSFRS-R score at month 6 compared to placebo (mean difference 1.01, 95%CI −0.87 to 3.09, p = 0.293), as shown by evidence from RCTs. However, observational studies did not show any benefit of adding edaravone to routine practice (mean difference 1.85, 95%CI −2.05 to 5.75, p = 0.352). The change from baseline in ALSFRS-R score was −2.1, −4.04, −7.5, −6.82, and −7.9 at months 3, 6, 9, 12, and 18, respectively. The GRADE assessment indicated moderate certainty for evidence from RCTs, while evidence from observational studies had very low certainty. Conclusion Due to the limited number of studies and confounding issues in observational studies, further examination of the added benefits of edaravone to routine practice is necessary through RCTs, particularly regarding its long-term efficacy.